Towards autonomous robotic systems 12th annual conference, TAROS 2011, Sheffield, UK, August 31 - September 2, 2011. Proceedings - Groß, Roderich; Alboul, Lyuba; Melhuish, Chris; Witkowski, Mark; Prescott, Tony J; Penders, Jacques (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 12th Annual Conference Towards Autonomous Robotics Systems, TAROS 2011, held in Sheffield, UK, in August/September 2011. The 32 revised full papers presented together with 29 two-page abstracts were carefully reviewed and selected from 94 submissions. Among the topics addressed are robot navigation, robot learning, human-robot interaction, robot control, mobile robots, reinforcement learning, robot vehicles, swarm robotic systems, etc.